Decarbonization pathways for remote amazonian communities : life cycle assessment and carbon dynamics of wood waste-based bioenergy system - Oliveira, Paloma Fachinelli de (2025)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, Programa de Pós-Graduação em Ciências Mecânicas, 2025.